Strengths, weaknesses, opportunities and threats in coastal women's health management: A systematic review - Meylanzharie, Zhulvie; Iswahyudi, Iswahyudi (Institute for Research and Community Service (LPPM), Universitas Islam Madura, Indonesia, 2025)
Coastal women's health problems are one aspect of improving the standard of living of coastal communities. This research aims to conduct a systematic review of strengths, weaknesses, opportunities, and threats (SWOT) in managing coastal women's health. This research method involves a thorough analysis of scientific literature related to coastal women's health from Scopus sources. A systematic review was used in this research on the publication of 34 articles on coastal women's health. The results of the analysis show that the strength of coastal women's health management lies in the active participation of coastal women in disease prevention communities, providing immunizations to pregnant women, providing postnatal care, and providing breast milk to babies who are born. However, weaknesses include limited access to health services and reproductive health education, especially in areas with difficult geographic conditions. Opportunities in managing coastal women's health can be found in community empowerment, increasing accessibility to health services, and collaborative cross-sector approaches. The main threats involve the impacts of climate change, environmental pollution, and inequities in the distribution of health resources. Therefore, this systematic review provides a comprehensive understanding of the factors influencing coastal women's health and provides a basis for the development of more effective policies and interventions in the future.